Bowel preparation in intravenous urography doesnt have an impact on the quality of urinary tract image (Bangladesh Journal of Medical Science, 2017)
Purpose: The procedure of bowel preparation before intravenous urography (IVU) is still a controversial debate and it varies in each health center. Preparation is believed to reduce residual feces and intestinal gas thus improving the quality of visualization of the urinary tract. On the other hand, many radiology and urology studies did not mention the need for preparation before IVU procedure. Preparation before IVU, especially giving laxative agent, gives many adverse effects to the patient. The purpose of this study was to know the difference in quality visualization of the urinary tract in IVU patients with and without preparation in Saiful Anwar hospital Malang.Materials and Methods: A total of 20 patients participated in this study and they were divided into two groups in which each group consists of 10 patients with and without preparation before IVU. Abdominal x-ray and IVU were performed on all patients. Urinary tract visualization quality assessment was done through two methods of assessing the quality of the image by the European Commission Guidelines and of assessing the residue of feces/ intestinal gas based on Dadkhahs studies.Results: Results showed the total score of image quality and the residue of feces/intestinal gas was not significantly different in the abdominal plain photo of IVU patients with and without preparation (Mann-Whitney test (p=1.000) and Independent T-test (p=0.5111)).Conclusions: In conclusion, there was no difference in the quality of visualization of the urinary tract in IVU patients with and without preparation in Saiful Anwar hospital Malang.Bangladesh Journal of Medical Science Vol.16(1) 2017 p.107-114